Assessing MyPlate Familiarity and Typical Meal Composition using Food Models in Children Aged 7-13 - Willis, Jada L.; Howe, Carol J.; Alexander, Gina K. (International Journal of Child Health and Nutrition, 2019)
The Dietary Guidelines for Americans serve as a basis for developing federal nutrition education materials for the public, such as MyPlate. MyPlate is a visual cue that uses food groups as a guide to building healthy plates at mealtime. The objective of this study was to determine factors associated with child familiarity with MyPlate guidelines and to determine if typical meals met MyPlate guidelines using food models. A convenience sample of 250 children (aged 7-13 years) and their parent/guardian were recruited at a local science and history museum. Children viewed a picture of the MyPlate icon and were asked to identify the picture. Next, participants used a nine-inch plate to build a typical meal (meals that they would regularly consume) from a buffet of food and beverages models (>65 items to choose from). Research team members took photographs of the plates. A Registered Dietitian Nutritionist determined the percentage of plates that met MyPlate guidelines. Eighty-six percent of children recognized the MyPlate icon upon viewing the image; 7.6% could accurately identify the icon by name. When participants were asked to build a typical meal, however, only 3.43% met MyPlate guidelines. The results of this study suggest that despite being familiar with MyPlate, children built typical meals that did not meet MyPlate guidelines.